INFECTIOUS DISEASES OF AFGHAN IMMIGRANTS IN THE UNITED STATES: REVIEW OF PUBLISHED REPORTS - Pilsczek, Florian H (Journal of Ayub Medical College Abbottabad, 2011)
Infectious diseases of immigrants may differ from patients born and resident in the same country, especially if immigrants from Africa or Asia live in Europe or North America. Because the available information is limited published reports of infections of Afghan immigrants in the United States and other countries were analysed. Four reports from the US and 15 reports from other countries were identified [7, (46.7%) Pakistan, 5 (33.3%) Iran, 1 (6.7%) United Kingdom, 1 (6.7%) Germany, 1 (6.7%) Israel)]. Reports from the US were case reports or case series of infections with gastro-intestinal parasites and Mycobacterium tuberculosis (1, 25%), Echinococcus species (2, 50%), and Plasmodium vivax (1, 25%). Reports from other countries were case reports, case series, or surveys and investigated infections with Echinococcus species (2, 13%), Hepatitis B virus (HBV) (1, 6.7%), M. tuberculosis (6, 40%), P. falciparum (1, 6.7%), Leishmania tropica (3, 20%), Fasciola hepatica (1, 6.7%), and M. leprae (1, 6.7%). The reports suggest that Echinococcus species and L. tropica infections can be encountered in Afghan immigrants in the US, and the frequency of a positive PPD (purified protein derivative) response or HBsAg test was increased. An infectious diseases database specific for the country of residence readily available to clinicians treating Afghan patients outside of Afghanistan may be useful. Keywords: International Health, Immigrants, Afghanistan